2014
DOI: 10.1021/ac502390c
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody-Based Enzyme Immunoassay for Aflatoxin in Agro-Products with High Tolerance to Cosolvent Methanol

Abstract: A phage-displayed library of variable domain of heavy chain of the heavy chain antibody (VHH) or nanobody (Nb) was constructed after immunizing an alpaca with aflatoxin B1 (AFB1) conjugated with bovine serum albumin (AFB1-BSA). Two AFB1-specific nanobodies were selected. The obtained nanobodies were compared to an aflatoxin-specific monoclonal antibody B5 with respect to stability under organic solvents and high temperature. The two nanobodies could bind antigen specifically after exposure to temperatures as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 29 publications
1
112
1
Order By: Relevance
“…Solvent contents in the sample often change the analytical parameters of an immunoassay (He et al, 2014;Mercader & AbadFuentes, 2009). Fermented drinks like wine or cider may contain important concentrations of ethanol, so the influence of alcohol over the inhibition curve of the proposed cELISAs needs to be evaluated.…”
Section: Alcohol Tolerancementioning
confidence: 99%
“…Solvent contents in the sample often change the analytical parameters of an immunoassay (He et al, 2014;Mercader & AbadFuentes, 2009). Fermented drinks like wine or cider may contain important concentrations of ethanol, so the influence of alcohol over the inhibition curve of the proposed cELISAs needs to be evaluated.…”
Section: Alcohol Tolerancementioning
confidence: 99%
“…Compared to the conventional antibody fragments, the evolution of hydrophilic amino acids within framwork 2 of the heavy chain variable domain contributes to the high water solubility of nanobodies [9]. Due to their unique properties, more and more nanobodies for toxic and harmful substances were isolated and used as the detection reagent of immunoassays in food analysis [13, 14]. In addition, Nbs are readily genetically manipulated to construct fusions with green fluorescence protein and alkaline phosphatase [1517], thus expanding their applications in immunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin B 1 (AFB 1 ) is the most toxic, and one of the most potent carcinogens in nature. In this study [39], the VHH antibodies were selected using gradually decreasing concentrations of AFB 1 −BSA conjugate and free AFB 1 and more stringent washing. Two unique clones, named Nb26 and Nb28, were selected.…”
Section: Summary Of Vhh Assays To Environmental Chemicalsmentioning
confidence: 99%
“…Similar results were observed with DMSO. The VHHs for aflatoxin described by He et al [39] were evaluated in the presence of MeOH, DMSO, dimethylformamide (DMF), acetone and acetonitrile. The data indicated that the VHHs and mAbs were remarkably resistant to acetone.…”
Section: Advantages Of Vhhsmentioning
confidence: 99%